2004
DOI: 10.1097/01.jom.0000111603.84316.0f
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in US Air Force Veterans of the Vietnam War

Abstract: Cancer incidence and mortality were summarized in Air Force veterans of the Vietnam War. The index subjects were Operation Ranch Hand veterans who sprayed 2,3,7,8 tetrachlorodibenzo-p-dioxin (dioxin)-contaminated herbicides in Vietnam. Comparisons served in Southeast Asia during the same period but did not spray herbicides. We assessed cancer incidence and mortality using national rates and contrasted cancer risk in each of three Ranch Hand dioxin exposure categories relative to comparisons. The incidence of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 77 publications
(42 reference statements)
2
87
2
1
Order By: Relevance
“…While we did not find a difference in the risk of prostate cancer between Ranch Hand and Comparison veterans in this study, a recent comparison of cancer incidence in this cohort relative to the general United States white population found a positive association with prostate cancer in both groups of veterans (standardized incidence ratio F SIR ¼ 1.46 in Ranch Hand and SIR ¼ 1.62 in Comparison veterans) (Akhtar et al, 2004). Air Force veterans have been more closely followed than the general population and underwent repeated medical examinations that may partly explain excesses seen in that study.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…While we did not find a difference in the risk of prostate cancer between Ranch Hand and Comparison veterans in this study, a recent comparison of cancer incidence in this cohort relative to the general United States white population found a positive association with prostate cancer in both groups of veterans (standardized incidence ratio F SIR ¼ 1.46 in Ranch Hand and SIR ¼ 1.62 in Comparison veterans) (Akhtar et al, 2004). Air Force veterans have been more closely followed than the general population and underwent repeated medical examinations that may partly explain excesses seen in that study.…”
Section: Discussioncontrasting
confidence: 39%
“…Small numbers of prostate cancer cases and a lack of individual exposure assessments were the main weaknesses of these veterans' studies. Earlier results from the AFHS did not reveal an excess of prostate cancer (Ketchum et al, 1999;AFHS, 2000) but recent study reported excess of prostate cancer in comparison to the standard US white male population (Akhtar et al, 2004).…”
Section: Introductionmentioning
confidence: 93%
“…Relatively few studies have been conducted to look for specific environmental risk factors for melanoma, but among these, a number of studies have shown an elevated risk in individuals with suspected exposure to organochlorine compounds, such as polychlorinated biphenyls (PCBs) and some chlorine-based pesticides [1,146,161,198,203,207,208,220,240,248]. As noted above, although these studies have some significant limitations, the results, with few exceptions, for implied industrial PCB exposure have been fairly consistently positive.…”
Section: Pcbsmentioning
confidence: 99%
“…Recent studies on the relationship between Agent Orange and prostate cancer have focused on US veterans of the Vietnam War (Ketchum NS et al 1998;Zafar MB et al 2001;Akhtar FZ et al 2004;Giri VN et al 2004;Justine L et al 2006;Pavuk M et al 2006;Chamie K et al 2008). However, only one study has focused on the relationship between PSA and Agent Orange in Vietnamese men (Sun XL et al 2013).…”
Section: Introductionmentioning
confidence: 99%